12 Cardiovascular magnetic resonance has a significant role in the management of acute heart failure admissions: a tertiary referral service experience. (28th January 2023) - Hampal, Rumneek; Knott, Kristopher D; O'Sullivan, Corry; Bunce, Nicholas H
Abstract : Introduction: Cardiac MRI is a vital tool in the assessment of heart failure. We investigated the utility of CMR on inpatients admitted to our dedicated heart failure unit (HFU, the first in the UK). Materials and Methods: Patients admitted to our HFU and referred for inpatient CMR from August 2018 – August 2022 were included. Data was collected retrospectively from the electronic patient records including patient demographics, co-morbidities, CMR findings and subsequent major adverse cardiovascular events (MACE). Results: 85 patients were included, 64 (75%) male, mean age 69(±13)years, 26% had an existing diagnosis of heart failure. The primary reason for admission was decompensated heart failure in 80% patients. There were 66 (78%) patients with HFrEF (EF <40%), 7 (8%) with HFmrEF (EF 40–50%) and 12 (14%) with HFpEF (EF >50%). The indication for CMR was to assess the aetiology of heart failure in 48 (56%) patients. 65 (76%) patients had an invasive coronary angiogram during their acute admission. CMR was performed in 78 patients, 6 did not tolerate the scan and late gadolinium enhancement was non-diagnostic in 1 patient. The aetiology of heart failure was ischaemic in 24 (31%) patients and non-ischaemic in 51 (65%) patients, 3 (4%) patients had mixed ICM/NICM. Of the 27 (35%) patients with infarct, 19 (70%) had invasive coronary angiography and 7 were revascularized (26%). In those without infarct, 39 patients had invasive coronary assessment (76%) and none were revascularized. CMR changed management in 54 (64%) patients including change in medication (53/54, 98%) and device therapy (7/54, 13%). 12 (14%) patients were re-admitted within 30 days. There were MACE in 5 (6%) patients including decompensated heart failure, arrhythmia (VT) and stroke, 2 (2%) died during admission and 3 (4%) patients died within 90 days following discharge. Discussion: CMR has a significant impact on the management of patients admitted to a specialist HFU, more so than coronary angiography and informed further management decisions regarding medication changes, re-vascularisation strategies and device implantation. Conclusion: CMR has a vital role in the management of inpatients with acute heart failure enabling accurate diagnosis and facilitating a tailored management approach.